Giant Cane Vegetative Buffer for Improving Soil and Surface Water Quality. Issue 2 (1st March 2019) - Singh, Gurbir; Schoonover, Jon E.; Williard, Karl W. J.; Sweet, Audrey L.; Stewart, Jonathan
Abstract : Over the past four decades, riparian buffers have proven effective in retaining nutrients and sediment from agricultural runoff. Many grass species have been used with variable success in riparian buffers to improve the water quality of runoff. However, limited information is available on the effectiveness of giant cane [ Arundinaria gigantea (Walt.) Muhl] in improving surface water quality compared with grass species such as Kentucky bluegrass ( Poa pratensis L.) and orchardgrass ( Dactylis glomerata L.). Therefore, the objective of our study was to determine the quality of runoff leaving vegetative buffer plots planted with giant cane, Kentucky bluegrass, and orchardgrass. Additionally, a bare‐ground control and continuous corn ( Zea mays L.) was also monitored for comparison of runoff with vegetative buffers. The giant cane treatment had significantly greater infiltration rates (38.18 mm h −1, p < 0.05) than bare ground (1.61 mm h −1 ), corn (5.75 mm h −1 ), Kentucky bluegrass (12.30 mm h −1 ), and orchardgrass (4.21 mm h −1 ) treatments. Dissolved reactive P in runoff was ranked as follows: corn > giant cane = Kentucky bluegrass = orchardgrass > bare ground. The total P from the corn treatment (1.70 mg L −1, p < 0.05) was significantly higher than for bare ground (1.22 mg L −1 ), giant cane (0.69 mg L −1 ), Kentucky bluegrass (0.86 mg L −1 ), and orchardgrass (0.54 mg L −1 ). Giant cane, Kentucky bluegrass, and orchardgrass significantly reduced the total P concentration more than bare ground and corn. Results from this study demonstrate the utility of giant cane as a vegetated buffer to reduce nutrient and sediment concentrations in agricultural runoff. Core Ideas: Giant cane's dense rooting system increased soil porosity and infiltration. Water‐stable aggregates were highest under giant cane vegetative buffers. Total suspended solids were lowest for runoff in giant cane vegetative buffers.